Predicting Success of Growth Modulation Surgery in Late-onset Tibia Vara - William Scott Fravel; Trevor Morelock; Jill C. Flanagan (Journal of Limb Lengthening & Reconstruction, 2025)
Introduction: Growth modulation surgery with hemi-epiphyseal tether plating in late-onset tibia vara (LOTV) has variable results in prior literature. We sought to confirm that skeletal maturity, patient body mass index (BMI), and deformity severity could be used to predict the odds of deformity correction in our patient population. We also hypothesized that a larger, more rigid implant design would also predict success. Methods: We retrospectively reviewed patients with LOTV treated with lateral tension band plate (LTBP)-guided growth at a tertiary pediatric multihospital facility over a 10-year period. Pre- and postoperative radiographic deformity markers, implant data, and demographic data were recorded. Included patients had final radiographs for analysis at minimum 2-year follow-up or last radiographs prior to hardware removal/subsequent surgery. Treatment success was defined as normalization of varus alignment or any valgus overcorrection of the limb. Uni- and multivariate analysis was performed to identify odds of a successful outcome based on recorded risk and treatment factors. Results: Forty-seven patients (74 limbs) met our inclusion criteria for review. Sixty-one percent (45) of limbs were successfully treated. Severity of deformity, skeletal maturity, and preoperative BMI all significantly correlated with treatment outcome. A 1º increase in medial proximal tibial angle (MPTA) or 1º increase in valgus mechanical tibiofemoral angle increased the odds of successful treatment by 1.22 (P < 0.001) and 1.2 (P < 0.001), respectively. When adjusting for MPTA and preoperative BMI on multivariate analysis, >3 years of growth remaining increased odds of successful treatment 27.2 times (P = .001). Implant design (screw size, cannulated or solid screws, screw number, and plate type) did not correlate with odds of treatment success. Conclusion: In our patient cohort, less severe deformity, greater age of growth remaining, and decreased patient BMI all predicted treatment success of LOTV with LTBP which corroborates prior studies’ results. We were not able to find a significant treatment effect from different implant options; however, this effect may be limited by our sample size. This information gives helpful insight into narrow treatment indications with this technique for LOTV and provides families with better estimates of success based on preoperative risk factors.